Answer:
x = — 2 and y = 2
Step-by-step explanation:
3x – 4y = — 14 (1)
3x + 2y = — 2 (2)
Since the coefficient of x in both equation are the same, then elimination method will be best method to solve the problem.
This can be achieved as follows:
Subtract equation (1) from (2), we have
3x + 2y = — 2
— 3x – 4y = — 14
6y = 12
Divide both side by the coefficient of y i.e 6
y = 12/6
y = 2
Now, we can substitute the value y into any of the equation to get x. In this case, I will be making use of equation (2). You can verify by using equation (1)
3x + 2y = — 2
3x + 2(2) = —2
3x + 4 = —2
Collect like terms
3x = —2 — 4
3x = —6
Divide both side by the coefficient of x i.e 3
x = — 6/3
x = — 2
Therefore x = — 2 and y = 2